2018
DOI: 10.5326/jaaha-ms-6808
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Prognostic Significance of Neutrophil-to-Lymphocyte Ratio in Dogs with Septic Peritonitis

Abstract: Systemic inflammation is known to cause WBC abnormalities, specifically neutrophilia and lymphopenia. The neutrophil-to-lymphocyte ratio (NLR) is a simple and affordable biomarker that has been used in human clinical settings of sepsis but has not been investigated in veterinary species. We evaluated NLR in dogs with septic and nonseptic systemic inflammatory diseases and compared with a healthy dog population. An NLR ≥6 had an 84.39% sensitivity and 86.95% specificity to identify dogs with systemic inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 48 publications
1
74
2
Order By: Relevance
“…Two recent studies investigated the NLR in SIRS and septic peritonitis in dogs. 10,11 Both studies found elevated NLRs during inflammatory processes but found no associations with the disease severity or course of disease. 10 The results of our study confirm that the NLR is increased in dogs and cats with pancreatitis compared with that of healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two recent studies investigated the NLR in SIRS and septic peritonitis in dogs. 10,11 Both studies found elevated NLRs during inflammatory processes but found no associations with the disease severity or course of disease. 10 The results of our study confirm that the NLR is increased in dogs and cats with pancreatitis compared with that of healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…In veterinary medicine, NLRs were investigated in some studies of dogs with septic peritonitis or systemic inflammatory response syndrome (SIRS). 10,11 They compared NLRs in dogs with sepsis, nonseptic systemic inflammatory disease, and controls. The conclusions about the use of the NLR as a prognostic marker in cases of severe inflammatory processes in dogs were different.…”
Section: Introductionmentioning
confidence: 99%
“…These Sepsis-3 definitions incorporate a rapid organ failure assessment score (92), that has yet to be robustly examined in veterinary medicine. An equivalent redefinition of sepsis in veterinary medicine had not been undertaken and hence the SIRS criteria remain the best available strategy (93), and have been used in multiple studies of canine sepsis and of septic peritonitis specifically (6, 14, 94, 95). As such, they were considered to be a necessary component of the identification of the SP and NSA populations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, humans affected by OSA also demonstrate higher N/L ratio, positively correlated to the OSA severity 48 and mitigated by continuous positive airway pressure (CPAP) therapy 48 , 49 . Furthermore, high N/L ratios were reported in dogs affected by systemic inflammatory response syndrome 50 and septic peritonitis 51 , but not yet described in brachycephalic dogs. Therefore, we considered the existence of a subacute inflammatory status on brachycephalic dogs, which corroborates previously evidence that this syndrome leads to systemic inflammatory derangements 10 , 52 , and probably to consequences such as observed in humans with OSA.…”
Section: Discussionmentioning
confidence: 93%